1995
DOI: 10.1016/s0022-5347(01)67508-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent Alterations in beta-adrenergic Responsiveness of Rat Detrusor Smooth Muscle

Abstract: The relaxant effects of norepinephrine (NE, 10(-7) to 10(-4) M.) and isoproterenol (ISO, 10(-9) to 10(-4) M.) on maximal KCl-induced tonic contractions and the relaxant effects of ISO on contractions induced by electrical field stimulation (EFS) were measured in detrusor muscle strips obtained from 22-25 day, 90-95 day and 22-month-old male Fischer 344 rats. The maximum relaxant response to NE and ISO on KCl-induced tonic contractions decreased significantly with increasing age. The ED50 values for ISO, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…Although a number of studies have been published on age-related changes in bladder function, no consensus has been reached [1][2][3][4][5][6][7][8][9]. Chun et al [3] observed that, in the in vivo rat bladder, both the total micturition volume and the frequency of micturition are significantly greater in old than young rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have been published on age-related changes in bladder function, no consensus has been reached [1][2][3][4][5][6][7][8][9]. Chun et al [3] observed that, in the in vivo rat bladder, both the total micturition volume and the frequency of micturition are significantly greater in old than young rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have suggested that the aging process alters micturition dynamics in vivo and contractile strength in vitro in response to some neurotransmitters [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Bladder strips from OVX and old rats exhibit decreased responsiveness to cholinergic stimulation (Diep and Constantinou, 1999), decreased tetrodotoxin-sensitive ACh release from nerve fibers, and increased tetrodotoxin-insensitive basal and stretchevoked ACh release from the urothelium (Yoshida et al, 2007). Other studies demonstrated hormonal-and/or agerelated alterations in G proteins, ␤AR density, and/or ␤AR responsiveness (Nishimoto et al, 1995;Derweesh et al, 2000;Frazier et al, 2006). Increased levels of G i protein, which inhibits cAMP production, were suggested as an underlying mechanism for the decreased ␤AR-induced relaxation of the bladder in old (24 months) male Fisher 344 rats (Derweesh et al, 2000).…”
Section: ϫ12mentioning
confidence: 98%
“…Increased levels of G i protein, which inhibits cAMP production, were suggested as an underlying mechanism for the decreased ␤AR-induced relaxation of the bladder in old (24 months) male Fisher 344 rats (Derweesh et al, 2000). Bladder strips from old (Ͼ22 months) Fisher 344 (Nishimoto et al, 1995;Derweesh et al, 2000) or Wistar (Frazier et al, 2006) male rats were less relaxed by the nonselective ␤AR agonists isoproterenol or norepinephrine and by the selective ␤ 3 AR agonists (BRL37344 and CGP12177) than bladder strips from young rats. However, other studies found no change in isoproterenol or norepinephrine-induced relaxation of bladder strips from 10-and 30-month-old female Wistar/Rij rats (Lluel et al, 2000).…”
Section: ϫ12mentioning
confidence: 99%
“…In contrast, there are some reports of age-related changes of the detrusor response to adrenergic stimulation (373). Some studies show that detrusor contractile responses to norepinephrine are increased in old male and female rats (473,531,532). Aged female rats also exhibit increases in expression of α 1D -adrenoceptors and α 1D -receptormediated contractions of the bladder (193).…”
Section: Agingmentioning
confidence: 99%